Pengembangan Bahan Ajar Materi Trigonometri melalui Pendekatan Realistic Mathematics Education - Meika, Ika; Solikhah, E. Fidri Firdaushi; Yunitasari, Ika (SJME (Supremum Journal of Mathematics Education), 2023)
The purpose of this study was to develop teaching materials in the form of LKPD trigonometry materials through the RME approach. Research and development is carried out using the Design Based Research (DBR) method with the Plomp development model consisting of three stages, namely: Preliminary Research, Prototyping Stages and Assessment. This article is part of a research entitled "Development of Trigonometry Teaching Materials through Realistic Mathematics Education Approaches", which contains results and discussions at the preliminary research and prototyping stages (up to prototype-2). The research was conducted at MAS Mathla'ul Anwar Center. The research begins with a needs analysis in the field, then continues with the creation of LKPD. The worksheets are validated by material experts and linguists. The validation results from material experts are 91.83% with a very valid category and from linguists the validation percentage is 75% with a fairly valid category and needs minor revisions. The results of the LKPD validation by the validator show that the LKPD is feasible to be tested on students with an average percentage of 86.25% with a very valid category. The revision of the validation stage resulted in prototype-1. The small group test was carried out on students of class XI IPA 2. The small group test produced prototype-2 which was ready to be used in classroom learning.